DEPRESSION, ANXIETY, STRESS, AND COPING MECHANISM DURING COVID-19 PANDEMIC - Alexandru-Filip POPOVICI (Studia Universitatis Babes-Bolyai, 2022)
The current pandemic due to the COVID-19 virus has caught the entire world by surprise, on all aspects of life, from economic and work-related ones to education and online communication. Psychological health issues are not an exception to this rule, as people have been forced to either stay indoors during lockdown periods, or completely change their habits for longer periods of time. In this study, we investigated the effects of the pandemic on a sample of 241 adults, on several concepts. The study is relevant for understanding the factors that can contribute to maintaining a balance in life, especially in times of hardship.